A review on antioxidants, prooxidants and related controversy: natural and synthetic compounds, screening and analysis methodologies and future perspectives - Carocho, Márcio (2013)
Many studies have been conducted with regard to free radicals, oxidative stress and antioxidant activity of food, giving antioxidants a prominent beneficial role, but, recently many authors have questioned their importance, whilst trying to understand the mechanisms behind oxidative stress. Many scientists defend that regardless of the quantity of ingested antioxidants, the absorption is very limited, and that in some cases prooxidants are beneficial to human health. The detection of antioxidant activity as well as specific antioxidant compounds can be carried out with a large number of different assays, all of them with advantages and disadvantages. The controversy around antioxidant in vivo benefits has become intense in the past few decades and the present review tries to shed some light on research on antioxidants (natural and synthetic) and prooxidants, showing the potential benefits and adverse effects of these opposing events, as well as their mechanisms of action and detection methodologies. It also identifies the limitations of antioxidants and provides a perspective on the likely future trends in this field.